Cerebral Stimulation for the Affective Component of Neuropathic Pain. Issue 6 (24th October 2012) - Machado, Andre G.; Baker, Kenneth B.; Plow, Ela; Malone, Donald A.
<x xml:space="preserve">Abstract</x> Objectives To review the current state of cerebral stimulation for neuropathic pain and to propose that cerebral stimulation should aim also at the affective sphere of chronic pain rather than solely focusing on the primary sensory‐discriminative sphere. Methods The past and current goals of cerebral stimulation are reviewed as well as its limitations. A novel deep brain stimulation approach is proposed to evaluate this conceptual shift from somatosensory to affective sphere of pain targeting. Approach Thalamic and other central pain syndromes are typically intractable to current treatment methods, including cerebral neuromodulation of somatosensory pathways, leading to long‐term distress and disability. Our modern understanding of chronic pain pathophysiology is based largely on the neuromatrix theory, where cognitive, affective, and sensory‐discriminative spheres contribute equally to the overall pain experience. During the last decade, the safety and feasibility of chronic stimulation of neural pathways related to mood and affect has been explored with promising results. Here, we propose a novel approach to modulate the affective sphere of chronic pain by targeting similar networks in patients with treatment‐refractory central pain. Our primary goal is not to produce (or measure) analgesia, but rather to modulate the affective burden of chronic pain. Discussion Cerebral neuromodulation for neuropathic pain has had limited efficacy thus far. Shifting our aim to neural networks related to the affective sphere of pain may allow us to reduce pain conditioning and pain‐related disability. Our ultimate goal is to promote rehabilitation from chronic pain—social and occupational.